2021
DOI: 10.1002/ijc.33821
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib treatment in a large real‐world cohort of nonsmall cell lung cancer patients with common and uncommon epidermal growth factor receptor mutation

Abstract: The epidermal growth factor receptor tyrosine kinase inhibitor (EGFR‐TKI) afatinib improves survival in nonsmall cell lung cancer (NSCLC) patients with EGFR mutation. We analysed the outcome between EGFR mutation subtypes in a large afatinib‐treated cohort in which 516 EGFR‐mutated NSCLC patients receiving afatinib as front‐line treatment. EGFR uncommon mutations include exon 20 insertion, de novo T790M of high or low allele frequency (dT790MHAF/dT790MLAF), non‐T790M compound mutation and others, where EGFR ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…EGFR exon 20ins are generally associated with de novo resistance to first-or second-generation EGFR-TKIs (6,33). Our result confirmed this concept, with a median PFS of only 2-3 months for this special subgroup (34).…”
Section: Discussionsupporting
confidence: 83%
“…EGFR exon 20ins are generally associated with de novo resistance to first-or second-generation EGFR-TKIs (6,33). Our result confirmed this concept, with a median PFS of only 2-3 months for this special subgroup (34).…”
Section: Discussionsupporting
confidence: 83%
“…In Taiwan, 1G/2G EGFR-TKIs, gefitinib, erlotinib, and afatinib are all commonly prescribed as frontline therapy for EGFR-mutated NSCLC patients [ 22 , 23 ]. Although a previous study reported that frontline EGFR-TKIs (gefitinib, erlotinib, and afatinib) had a statistically significant difference in the T790M mutation rate (59.9%, 45.5%, and 52.7%, respectively; p = 0.037) [ 24 ], there was no significant difference in the T790M mutation rate after frontline treatment with different EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted therapies, represented by epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs), have greatly improved the quality of life and prognosis of patients with non-small cell lung cancer (NSCLC) [ 2 ]. Patients carrying common EGFR mutations (including in-frame deletion mutations in exon 19 (19del) and missense mutations in exon 21 (L858R)) significantly benefit from EGFR-TKIs; however, because of the high heterogeneity of uncommon EGFR mutations (defined as mutations other than classical mutations), patients carrying such mutations differ dramatically in their sensitivity to TKIs [ 3 , 4 , 5 , 6 , 7 ]. In general, patients carrying uncommon EGFR mutations are less sensitive to TKIs than those harboring classical mutations and tend to have an unfavorable prognosis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%